Randomized trials - Ivermectin repurposing for COVID-19 treatment of outpatients with mild disease in primary health care centers - Chahla, Rossana (2022)
Objective: to evaluate the therapeutic intervention with Ivermectin in outpatients with COVID-19 mild disease, to increase medical discharge and prevent the progression to moderate or severe disease. Methods: Randomized Trial, n= 254. The subjects were divided into experimental (EG: n= 110) and control groups (CG: n= 144). The EG receivedm Ivermectin orally 0.6 mg/kg weight in two doses. All participants were by physical examination COVID-19 diagnosed with negative RT-PCR at the beginning and the end of protocol. Differences between the variables were determinedusing the Chi-square test (p<0.05). The contagion risk (Odds Ratio) was calculated using software STATA. Results: Both groups were similar in age, sex, and comorbidities. A significant reduction in the percentage of participants with symptoms (PPS) was observed in the EG and CG when the clinical evaluation of symptoms was performed from 5th to 9th day (p= 0.0005). When the clinical evaluation was performed from 10th to 14th day there was no significant difference. A higher proportion of medical discharge was observed in EG (98.2%) vs. CG (86.1%) (p= 0.0007). EG showed 8 times more chance of receiving medical discharge than CG (OR 8.71, 95% CI: 1·99 – 38.12, p= 0.004). The treatment effect with Ivermectin to obtain medical discharge from outpatient care was analyzed by logistic regression. Then, the chance to obtain medical discharge was independent of variables sex, age, and comorbidities. Conclusion: This work supports the potential efficacy of Ivermectin in outpatient care with mild COVID-19 as a potentially useful intervention of public health consideration.